2014
DOI: 10.1016/j.sab.2014.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Good practices in LIBS analysis: Review and advices

Abstract: International audienceThis paper presents a review on the analytical results obtained by laser-induced breakdown spectroscopy (LIBS). In the first part, results on identification and classification of samples are presented including the risk of misclas-sification, and in the second part, results on concentration measurement based on calibration are accompanied with significant figures of merit including the concept of accuracy. Both univariate and multivariate approaches are discussed with special emphasis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(122 citation statements)
references
References 99 publications
1
109
0
2
Order By: Relevance
“…As has been pointed out by El Haddad et al [109], many LIBS publications still provide inadequate data on validation and performance. It has been suggested that the confusion matrix of the results should be presented in full and that figures of merit describing the success of classification and identification by a metric generally recognized (e.g.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…As has been pointed out by El Haddad et al [109], many LIBS publications still provide inadequate data on validation and performance. It has been suggested that the confusion matrix of the results should be presented in full and that figures of merit describing the success of classification and identification by a metric generally recognized (e.g.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…The leave-one-out (LOO) crossvalidation method [29][30][31][32] was used to find out the optimal set of spectral lines and to estimate the regression model predictivity. We used spectra of 36 pellets with nine different heating values for calibration, and for testing, we left out a subset of spectra of four pellets of the same sample having the known heating value from calorimetric measurements.…”
Section: Cross-validationmentioning
confidence: 99%
“…In Fig. 3, f sum (h) is the tting curve dened by eqn (6), which effectively ts the distribution of the coloured points. Once the expression of f(h) is ascertained, for any recorded I, the corresponding h could be calculated from the plasma image by eqn (1) and (3), and the intensity corresponding to the standard position could be described as…”
Section: Model Descriptionmentioning
confidence: 99%
“…1 Though LIBS has shown great potential in many different applications for its capacity in on-line, in situ analysis, [2][3][4][5][6][7][8] it is mostly used as a type of qualitative analysis or semiquantitative analysis, primarily because of its lack of stability in an ordinary measurement environment. In other words, poor measurement repeatability and reproducibility prevent LIBS from becoming a real super star like other established quantitative analysis techniques.…”
Section: Introductionmentioning
confidence: 99%